Computational design and cellular synthesis of two protein topological isomers: Solomon link vs. three-twist knot - Lianjie Xu; Xiaohui Song; Hua Xu; Wen-Hao Wu; Xiao-Dong Su; Wen-Bin Zhang (Proceedings of the National Academy of Sciences, 2026)
Chemical topology has emerged as a unique dimension in protein engineering, motivating the pursuit of topologically nontrivial protein architectures for functional advantages, such as enhanced stability and rich dynamics. However, the structural diversity of artificial mechanically interlocked proteins remains limited. Here, we report the computational design and cellular synthesis of a pair of topological isomers via symmetric assembly of orthogonal entangling motifs. By fusing two C 2 symmetric entangling motifs, i.e., p53dim and HP0242, in specific arrangements, we programmed the formation of multiple crossings, which upon cyclization yielded a protein Solomon link and a protein three-twist knot. The fusion patterns and linker lengths were systematically optimized to direct the formation of the intended topologies. Their successful cellular synthesis was validated through biophysical and structural analyses, including sodium dodecyl sulfate-polyacrylamide gel electrophoresis, size exclusion chromatography, and liquid chromatography-mass spectrometry. Notably, we report the crystal structure of an artificial protein three-twist knot. Both the Solomon link and the three-twist knot displayed increased structural compactness and stability relative to their controls with lower topological complexity (e.g., Hopf link, trefoil knot, and linear forms), as evidenced by their superior thermal stability and resistance to chemical denaturation. This modular design strategy provides a rational and extensible route to diverse mechanically interlocked proteins and could be generalized to access even more complex architectures, such as protein chainmail-like nanocages and woven protein frameworks.